The clinicopathological features of colorectal mucinous adenocarcinoma and a therapeutic strategy for the disease - Numata, Masakatsu (BioMed Central, 2012)
BACKGROUND: The guidelines established by the National Comprehensive Cancer Network do not describe mucinous histology as a clinical factor that should influence the therapeutic algorithm. However, previous studies show conflicting results regarding the prognosis of colorectal mucinous adenocarcinoma. In this study, we described the clinicopathological features of mucinous adenocarcinoma in Japan, to identify optimal therapeutic strategies. METHODS: 144 patients with mucinous and 2673 with non-mucinous adenocarcinomas who underwent primary resection in two major centers in Yokohama, Japan were retrospectively evaluated for clinicopathological features and treatment factors. A multivariate analysis for overall survival followed by the comparison of overall survival using Cox proportional hazard model were performed. RESULTS: Patients with mucinous adenocarcinoma had larger primary lesions, higher preoperative CEA levels, a deeper depth of invasion, higher rates of nodal and distant metastasis, and more metastatic sites. A multivariate analysis for overall survival revealed a mucinous histology to be an independent prognostic factor. In the subgroup analysis stratified by stage, Patients diagnosed as StageIII and IV disease had a worse survival in mucinous adenocarcinoma than non-mucinous, while survival did not differ significantly in patients diagnosed as Stage0-II disease. In StageIII, local recurrence in rectal cases and peritoneal dissemination were more frequently observed in patients with a mucinous histology. CONCLUSIONS: Our study indentified that mucinous adenocarcinoma was associated with a worse survival compared with non-mucinous in patients with StageIII and IV disease. In rectal StageIII disease with mucinous histology, additional therapy to control local recurrence followed by surgical resection may be a strategical alternative. Further molecular investigations considering genetic features of mucinous histology will lead to drug development and better management of peritoneal metastasis